Study of Association between Lipid Profile and Thyroid Hormones in Pregnancy - Ibrahem, Suhad abdulaziz; Ahmed, Salman A (Al-Nahrain Journal of Science, 2018)
Thyroid function during pregnancy is important for both the mother and the developing fetus. Especially during the first trimester, when the fetus is completely dependent on the mother for thyroid hormone. Increase liver metabolism is seen, renal plasma flow increases during pregnancy. This Study includes measurement of the thyroid hormones T3,T4,TSH and lipid profile, in serum of fifty pregnant women between 16-50 years during the three trimesters compared with serum of twenty non-pregnant women between 17-45 years. Results of pregnant women at first trimester showed that there was a significant difference at (P